Increase Sales Volume Through Marketing Mix at Balubur Town Square - Frans Sudirjo; Sandra Sriwendiah; Norvadewi Norvadewi; Kadeni Kadeni (SEIKO : Journal of Management & Business, 2023)
This study aims to determine the strategy of increasing sales volume through the marketing mix at Balubur Town Square (Baltos). The results showed that the products sold at Baltos were not as diverse as most of the women's and children's clothing, the prices offered were relatively the same for the same products, the location of Baltos was strategically located in downtown Balubur, sales promotion had not been maximized by Baltos towards the activities of selling its products, the buying and selling process takes place face to face at Baltos, the employees who work are workers who specifically sell clothes according to the products being sold, the arrangement of shops is not much different from one shop to another. The strategy that is expected to increase sales volume is to offer a wider variety of products at lower prices and to carry out more vigorous promotions to attract buyers. The buying and selling process should also be carried out online by utilizing skilled employees and displaying the uniqueness of the shop that sells the product. Keywords: Strength; Weakness; Opportunity; Threat; Marketing Mix.